MERETAS SISTEM PEMBELAJARAN PARADIGMA BARU - Pujiriyanto, Pujiriyanto (MAJALAH ILMIAH PEMBELAJARAN, 2011)
New educational paradigm is strongly needed for education reform inIndonesia. Educational system is influenced by the social system at macro,mezzo, and micro level as consequence education system must be respectiveand pro active to response the social system changes. The concepts ofworkplace, family, and society are change systematically. Industrial age isgoing to shif to information age society with different characteristic. Thereare two important aspects management and learning method. Educationmanagement should be more open to network for knowledge sharing. Thelearning methods should be change in order make the learner as the subjectof knowledge construction and be active participant in learning process. Theschool as education institution should develop partnership and networkwith others education institution.